Scenario of Key Factors Development in Betta Fish Micro-Business: Leverage and ISM Approach - Nugroho B. Sukamdani; Tatan Sukwika (Institute of Computer Science (IOCS), 2022)
Betta fish farming micro-business has good potential as an alternative income for the community, but few show the sustainability of their business. The purpose of this research is to design a scenario for future micro-business development strategies for betta fish business actors. The method of analysis uses data collected from questionnaires with micro business actors of betta ornamental fish. Testing the data used leverage test and Interpretative structural modelling (ISM). The results of the analysis showed that 18 attributes were the key factors and three scenarios of the betta micro business development strategy were obtained. The conclusion from the 18 key factors that become sub-elements obtained seven independent key factors, five linkages and six dependents. Each of the sub-elements in the three quadrants can be used as a key in formulating a scenario for the sustainability of the betta micro-business in the future.